Animal anthrax in Sirajganj district of Bangladesh from 2010 to 2012 (Asian Journal of Medical and Biological Research, 2016)
A descriptive study was conducted using secondary surveillance data of animal anthrax from the Epidemiology Unit of Department of Livestock Services (DLS) for the years 2010, 2011 and 2012. The objectives of this study were to describe the pattern of animal anthrax in Sirajgong district of Bangladesh from 2010 to 2012 and to assess the current use of anthrax vaccine (Vaccine Coverage) based on animal, time and place. The study found that the disease was more prevalent in this district at the beginning of the early monsoon (Month of May, June when flood water enters) and the late monsoon (Month of September, October, when flood water recedes). Cattle were the predominant animal species affected with anthrax in this district followed by goats and sheep. The overall mean case fatality rate was 30.19%. The numbers of reported anthrax outbreaks in cattle had declined each year with 111 in 2010, 32 in 2011 and 20 in 2012. The annual mean vaccination coverage during the same years was 44.29%, 46.23% and 37.88% respectively. To reduce the number of outbreaks in animals and humans in Sirajganj district the annual vaccination coverage requires improvement. Behavior change through building greater awareness of anthrax is also needed at the farmer level for control and eradication of anthrax in animals as well as human.Asian J. Med. Biol. Res. December 2015, 1(3): 387-395